Legal Protection of Wages and Welfare of Journalists in the City of Semarang - Syarif, Munif Ibnu Fatchu (Walisongo Law Review (Walrev), 2021)
This study analyzes the legal protection of wages and welfare of journalists in the City of Semarang. The purpose of the study was to determine the implementation of wages and welfare of journalists as well as legal protection of wages and welfare of journalists in the city of Semarang. Journalists are included in the labor category, so for their services, they are entitled to receive wages. One of the problems that occur among journalists is the weak legal protection of wages and welfare when discussing employment issues in Indonesia. Wage protection is an important aspect of the workforce. Wage protection is the goal of workers/ laborers carrying out work to earn sufficient income to finance their lives, namely a decent living for humanity. As long as the worker/laborer does his job, he is entitled to remuneration which guarantees his life together with his family. The results of the study indicate that the implementation of wages and welfare of journalists is not following Law Number 13 of 2003 concerning Manpower and Government Regulation Number 78 of 2015 concerning Wages. The wage system is the main problem. Journalists' work is not understood as a work process that ends with earning a wage; there is no firmness in the provision of working hours, benefits, and health insurance. The absence of these problems makes journalists not a few who violate the code of ethics. Not a few companies set a wage policy considering the company's ability, Semarang media wage standards, and skills possessed. Aspects of legal protection related to wages and welfare are weak. This is because of the difference between the working conception of journalists and the working conception of workers/laborers as referred to in the Manpower Act and Government Regulations concerning Wages. Ideally, it is necessary to create a legal umbrella for the implementation of maximum legal protection for economic, social, and technical aspects based on the work characteristics of permanent journalists so that they will be able to optimize work to achieve the maximum role of the press. Penelitian ini menganalisis perlindungan hukum pengupahan dan kesejahteraan wartawan di Kota Semarang. Tujuan penelitian adalah mengetahui implementasi pengupahan dan kesejahteraan wartawan serta perlindungan hukum pengupahan dan kesejahteraan wartawan di Kota Semarang. Wartawan masuk dalam kategori tenaga kerja, sehingga atas jasanya berhak menerima upah. Salah satu masalah yang terjadi di kalangan wartawan adalah lemahnya perlindungan hukum pengupahan dan kesejahteraan, jika mengulas tentang masalah ketenagakerjaan di Indonesia. Perlindungan upah merupakan aspek penting bagi tenaga kerja. Perlindungan pengupahan merupakan tujuan dari pekerja/buruh melaksanakan pekerjaan untuk mendapatkan penghasilan cukup untuk membiayai kehidupannya, yaitu penghidupan yang layak bagi kemanusiaan. Selama pekerja/buruh melakukan pekerjaannya, ia berhak atas pengupahan yang menjamin kehidupannya bersama dengan keluarganya.Hasil penelitian menunjukkan bahwa pelaksanaan pengupahan dan kesejahteraan wartawan belum sesuai Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan dan Peraturan Pemerintah Nomor 78 Tahun 2015 tentang Pengupahan. Sistem pengupahan adalah masalah utamanya. Kerja wartawan tidak dipahami sebagai proses kerja yang berakhir dengan perolehan upah; tidak ada ketegasan pemberian jam kerja, tunjangan dan jaminan kesehatan. Tiadanya masalah itu membuat wartawan tidak sedikit yang melanggar kode etik. Tidak sedikit perusahaan menetapkan kebijakan upah melihat kemampuan perusahaan, standar upah media Semarang dan keterampilan yang dimiliki. Aspek perlindungan hukum yang berhubungan dengan pengupahan dan kesejahteraan lemah. Hal ini karena perbedaan konsepsi kerja wartawan dengan konsepsi kerja pekerja/buruh sebagaimana dimaksud dalam Undang-Undang Ketenagakerjaan maupun Peraturan Pemerintah tentang Pengupahan. Idealnya perlu dibuatkan payung hukum demi terlaksanakannya perlindungan hukum yang maksimal terhadap aspek ekonomi, sosial dan teknis yang didasarkan pada karakteristik kerja wartawan tetap sehingga akan dapat mengoptimalkan kerja demi tercapainya peranan pers yang maksimal.